Selenium concentration and cardiovascular disease risk: Mendelian randomization study. (3rd October 2022) - Yuan, S; Mason, A M; Bruzelius, M; Akesson, A; Burgess, S; Larsson, S C
Abstract: Background/Introduction: Selenium has been associated with cardiovascular disease (CVD) risk in observational studies; however, the causality of the association remains unestablished. Purpose: To examine the associations of selenium concentrations with 15 CVDs using Mendelian randomization analysis. Methods: Genetic variants significantly associated with concentrations of toenail and blood (TAB) and blood selenium in mild linkage disequilibrium (r2 <0.3) were used as instrumental variables. Summary-level data for 15 CVDs were obtained from the UK Biobank study (n=367, 561), FinnGen study (n=218, 792), and six international consortia. The inverse variance weighted method accounting for linkage disequilibrium was used to estimate the associations. Results for one outcome from different sources were combined using the fixed effect meta-analysis method. Bonferroni correction was used to account for multiple testing, and associations with P value ≤0.003 (0.05 / 15 outcomes) were described as significant. Associations with P value between ≤0.05 and >0.003 were regarded as suggestive associations. Results: Genetically predicted concentrations of TAB selenium were not significantly associated with the risk of the 15 CVDs. However, there were suggestive associations of genetically predicted higher concentrations of TAB selenium with increased risk of atrial fibrillation and peripheral artery disease. The odds ratio per one-unit increase in log-transformed concentrations of TAB selenium was 1.07 (95% confidence interval, 1.01–1.12; P=0.019) for atrial fibrillation and 1.20 (95% confidence interval, 1.05–1.38; P=0.008) for peripheral artery disease. We observed no associations between genetically predicted blood selenium concentrations and risk of the 15 CVDs. Conclusions: Genetically predicted higher concentrations of TAB or blood selenium were not associated with a lower risk of CVD, which suggests that high selenium status may not prevent CVD development. The suggestive positive associations of TAB selenium with atrial fibrillation and peripheral artery disease warrants verification. Funding Acknowledgement: Type of funding sources: None.